Interaction of Copper with Imidazole in Presence of Dicarboxylic Acids. - DEV DAS, P.; DAS MANWAL , DEV (Asian Journal of Chemistry, 2010)
The interaction of Cu(II) with imidazole in presence of dicarboxylic acids, aminopolycarboxylic acids, maleic and fumaric acids has been investigated by a potentiometric method. The ternary complexes of amino polycarboxylic acids have Δ log K values less negative than the ternary complexes involving dicarboxylic acids, maleic and furmaric acids, Probable explanations for these are provided.